Risk in decentralised communications - Hussain, Omar; Chang, Elizabeth; Hussain, Farookh; Dillon, Tharam S.; Soh, B. (IEEE, 2005)
Risk is associated with almost every activity that is done in daily life. Analyzing the Risk involved in a transaction is important to decide whether to proceed with the transaction or not. Till now, Risk has been discussed extensively in the area of Investment, Finance, Health, Environment, daily life activities and Engineering. All these areas have different interpretations of Risk, which is not suitable to apply to a transaction in the area of Computer Science. In this paper we focus on defining Risk in a decentralized transaction in e-commerce.